Plaque control improves the painful symptoms of oral lichen planus gingival lesions. A short-term study - Salgado, Daniela S. [UNESP]; Jeremias, Fabiano [UNESP]; Capela, Marisa Veiga [UNESP]; Onofre, Mirian A. [UNESP]; Massucato, Elaine Maria Sgavioli [UNESP]; Orrico, Silvana R. P. [UNESP] (Wiley-Blackwell, 2013)
BackgroundLichen planus is a mucocutaneous disease with manifestation in the oral mucosa, the gingiva being one of the most affected regions. In some cases, the lesion may be painful and lead to fragility of the tissues, so that precise diagnosis and adequate treatment are indispensible factors for improving the clinical condition. The aim of this study was to evaluate the effectiveness of plaque control in the improvement of clinical features and painful symptoms of oral lichen planus with gingival involvement.MethodsTwenty patients diagnosed with gingival lichen planus confirmed by histopathological examination were selected. The patients were evaluated by a trained examiner, with regard to the clinical features of the lesions [Index of Escudier etal. (Br J Dermatol, 157, 2007, 765)]; painful symptoms (Visual Analog Scale); and periodontally, as regards the visible plaque and gingival bleeding indices. Periodontal treatment consisted of supragingival scaling and oral hygiene instruction, with professional plaque removal afterward for a period of 4weeks. The entire sample was evaluated at the baseline and at the conclusion of treatment, and the results were analyzed by the Wilcoxon nonparametric test.ResultsThe data demonstrated that the majority of patients were women (90%), with a mean age of 55.9years. Periodontal treatment resulted in statistically significant reduction (P<0.05) in the periodontal indices, with consequent improvement in the clinical features and painful symptoms of the lesions.ConclusionsIt was demonstrated that plaque control was effective in improving the clinical features and painful symptoms of oral lichen planus with gingival involvement.
Keywords: dental plaque; gingiva; oral lichen planus; periodontal treatment